PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Saiful Fajar Dwi Ananda; An Nuril Maulida Fauziah (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
This study aimed to describe the learning activities, a changes in the results of students' critical thinking skills after using a problem based learning model, and student responses after participating with problem based learning on model temperature and heat subject. This research method used pre-experimental design with one group pretest and post-test with the research target of 36 students from class VII-E 2nd Taman Junior High School. Observation, tests, and questionnaires obtained the data, and then analyzed on the descriptive quantitative method. The results showed that the category was very good in the percentage of learning implementation, with a value of 4 for 2 weeks of meetings. The critical thinking ability of students is fairly high, this is indicated by the N-Gain score obtained with high criteria of 97% (35 students) while students who are on the medium N-Gain criteria are 3% (1 student). The results of the questionnaire on student responses to learning were 90.37 with very good categories. This study concluded that the application of the problem-based learning model could improve critical thinking skills in the matter of temperature and heat. This research contributes to expanding and enriching the treasures of science learning and the study of problem-based learning and is expected to be applied by teachers in improving the quality and achievement of students' learning, especially critical thinking skills in science learning in the classroom.